2019
DOI: 10.3390/su11246892
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Investment Attractiveness in European Countries by Artificial Neural Networks: What Competences are Needed to Make a Decision on Collective Well-Being?

Abstract: A rich volume of literature has analysed country investment attractiveness in a wide range of contexts. The research has mostly focused on traditional economic concepts—economic, social, managerial, governmental, and geopolitical determinants—with a lack of focus on the smartness approach. Smartness is a social construct, which means that it has no objective presence but is “defined into existence”. It cannot be touched or measured based on uniform criteria but, rather, on the ones that are collectively agreed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…The role of financial development in promoting economic growth has been unanimously recognised by scholars at home and abroad [ 1 3 ] and it was found that the scale and function of finance can effectively stimulate long-term economic growth as well as total factor productivity growth through their studies. The main emphasis is on a kind of guiding effect of financial development on supply, that is, with the growth rate of economic development as well as the complexity of economic structure, social demand for financial aspects will further stimulate the development of the economy, and financial development and economic growth are causally related to each other [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of financial development in promoting economic growth has been unanimously recognised by scholars at home and abroad [ 1 3 ] and it was found that the scale and function of finance can effectively stimulate long-term economic growth as well as total factor productivity growth through their studies. The main emphasis is on a kind of guiding effect of financial development on supply, that is, with the growth rate of economic development as well as the complexity of economic structure, social demand for financial aspects will further stimulate the development of the economy, and financial development and economic growth are causally related to each other [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forty-seven documents were identified. Documents related to the health area (Lamberti et al, 2019;McNamara et al, 2019;Shorey et al, 2019;Rajadhyaksha, 2020;Zhao et al, 2020;Cheng et al, 2022;Creed et al, 2022;Liaw et al, 2022;Lokala et al, 2022;Shah et al, 2023), industry (Barykin et al, 2020;Mokhtarname et al, 2020;Sandner et al, 2020;Dmitrievsky et al, 2022;Obermayer et al, 2022;Zakharkina et al, 2022), education (Hrich et al, 2019;Tsalapatas et al, 2019;Cortés et al, 2020;Paba-Medina et al, 2020;Raj et al, 2020;Yang et al, 2020;Demchenko et al, 2021;Hurajová, 2021;Jiang, 2021;Petrescu et al, 2021Ghnemat et al, 2022Polak et al, 2022;Ramírez-Montoya et al, 2022;Rataj and Wojcik, 2022), science (Bruneckiene et al, 2019;Desnos et al, 2022;Ramírez-Montoya et al, 2022;Zhu et al, 2022), evaluation (Kiran et al, 2019;Prom et al, 2019;Konys, 2020;Bachiri and Mouncif, 2023;Rashidi Fathabadi et al, 2023), engineering (Kaspar and Vielhaber, 2019;Telnov and Korovin, 2019)...…”
Section: Adapted Work For the Building Of The Ideathonmentioning
confidence: 99%
“…Such soft determinants as entrepreneurship (Korez-Vide and Tominc, 2016; Kumar and Dahiya, 2017), learning (Jucevicius and Juceviciene, 2015), managerial discretion (Haj Youssef and Teng, 2019), clusters and networking (Evans, 2019) are distinguished as the determinants of SED. The smartness approach is essential to improve governance and economic efficiency (Caragliu et al , 2011), increase investment attractiveness (Bruneckienė et al , 2019; Snieska et al , 2019), sustainable development (Martin et al , 2018; Gazzola et al , 2019) and competitiveness (Kumar and Dahiya, 2017). The smartness approach in economic development has a significant effect on industrial theory (Piirainen et al , 2017) and urban development theory by developing smart (Gazzola et al , 2019) or ubiquitous (Lee et al , 2008) cities and on institutional theory by developing networking among corporate and governmental institutions (Bakici et al , 2013; Mora et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%